Computational Fluid Dynamics (CFD) interpretation of backfill pipeline system damage caused by paste-like slurry in water hammers - Hao Wang; Yuxin Hao; Zhongmin Ji; Zihan Tang; Ding Pengchu (PLoS ONE, 2025)
Paste-like slurry which made up of gangue particles and fly ash consolidated in the goaf could effectively reduce surface subsidence and improve resource recovery. The technology relies on efficient transport. However, there are many pipeline explosion accidents caused by water hammer due to rapid valve closure. The density and elasticity modulus of the paste-like slurry are significantly greater than other fluids. That makes the pressure exerted on the pipeline and valve by the slurry water hammer is significantly greater than the other fluids. The research established the relationship between valve closing time and peak pressure using dynamic meshes combining theoretical analysis and numerical simulations. The results show that the velocity at which the valve closes significantly affects the pressure on the valve and nearby pipelines. However, when the valve large open, the impact only on the local flow velocity and has no substantial impact on the flow state throughout the system. Finally, the optimal closing time of the butterfly valve was determined by comparing pressure magnitudes.. The paper focuses on the phenomenon of water hammer in dense slurries, which is different from other fluids. However, theoretical and simulation models have reference value for the study of other fluid water hammer.